Sol-gel preparation of a di-ureasil electrolyte doped with lithium perchlorate - Silva, Maria Manuela (2006)
Solid polymer electrolytes (SPEs) synthesized by the sol-gel process and designated as ormolytes (organically modified electrolytes), have been prepared through the incorporation of lithium perchlorate, LiClO4 into the U(2000) organic-inorganic hybrid network. Electrolytes with lithium salt compositions of n (where n indicates the number of oxyethylene units per Li+ ion) between ∞ and 0.5 were characterized by conductivity measurements, cyclic voltammetry at a gold microelectrode, thermal analysis and spectroscopic techniques. The conductivity results obtained suggest that this system offers a quite significant improvement over previously characterized analogues doped with lithium triflate.